Holy Land, Whose Land: Modern Dilemma, Ancient Roots? by Dorothy Drummond (Seattle: Educare Press, 2002. 326 pages.) (American Journal of Islam and Society, 2003)
Dorothy Drummond's book was born at the dawn of the third millennium,when the author was in Jerusalem. She had taken notes throughout hertravels in the Holy Land, which she defines not only as the land of historicPalestine, but also the lands of present-day Lebanon, Jordan, Syria, Iraq,and Egypt (i.e., where the Patriarchs, Prophets, and the Holy Familyroamed). Rather than write a travelogue, she decided to write a book aboutthe Arab-Israeli conflict while interspersing her personal comments (initalics) about her journeys. Her intent is not to "answer the question posedin the title of this book. Rather, by shedding light on dark corners, itattempts to bring understanding," as she explains in the prologue.The book is divided into three parts: a discussion of the IsraeliPalestinianconflict in the present, a discussion of the roots of the conflicttraveling 4,000 years into the past, and a brief discussion of how negotiationis the only way to resolve the conflict. There are maps and pho tographsthroughout the book, as well as a 40-page glossary of the HolyLand's people and places. Drummond has written the work in the presenttense, because of the immediacy of all that has happened in the MiddleEast, but the discussion ultimately centers on the area between theMediterranean Sea and the Jordan River.Her book promises to be a good, balanced account written in a wonwonderfullyaccessible style. However, early on it runs into problems. Forexample, when she talks about the 1956 Israeli attack on Egypt, she fails ...